Shirley Chisholm : du conflit au pouvoir - Hélène Charlery (Anglophonia)
Shirley Chisholm is a pioneer in the history of black women in American politics. Her several campaigns first to the New York State Assembly, to the US Congress, and then to the White House, and her unpredicted elections or results, paved the way for future black and female candidates in politics because she had changed the image of representatives in Congress or in national politics. Mostly remembered as the first black woman elected to Congress and the first black presidential candidate, she made tremendous efforts to move forward generally forgotten social, racial and gender issues in the legislative political agenda.